2021
DOI: 10.52543/tjpp.16.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Whitefly Dialeurodes citri: A New Pest on Citrus in Tunisia?

Abstract: Whiteflies invaded citrus orchards in Tunisia in the 90’s. Two species: Aleurothixus floccosus and Parabemisia myricae have been recorded successively infesting citrus and causing severe damage in Cap-Bon (North-East of Tunisia). These pests were first controlled by several insecticidal applications but with a relative efficiency. Then two biological control programs have been deployed completing the action of native natural enemies especially for P. myricae. The result was a very satisfactory control of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Algeria, for example, is the fifth largest citrus producer in Africa with more than 1.478.053 tons generated from 71.470 ha (FAO, 2020). A major problem is that citrus products around the world have been affected by numerous insect pests (Uygun & Satar,2008), such as the citrus whitefly Dialeurodes citri (Wang et al, 2021, Butter & Dhawan, 2021, which can cause high yield losses due to sucking of plant sap by nymphs (Zhang & Li, 2012;Yuan et al, 2017;Boulahia-Kheder, 2021). Recently, Zhang et al (2019) reported that D. citri can be an effective vector for virus CYVCV to citrus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algeria, for example, is the fifth largest citrus producer in Africa with more than 1.478.053 tons generated from 71.470 ha (FAO, 2020). A major problem is that citrus products around the world have been affected by numerous insect pests (Uygun & Satar,2008), such as the citrus whitefly Dialeurodes citri (Wang et al, 2021, Butter & Dhawan, 2021, which can cause high yield losses due to sucking of plant sap by nymphs (Zhang & Li, 2012;Yuan et al, 2017;Boulahia-Kheder, 2021). Recently, Zhang et al (2019) reported that D. citri can be an effective vector for virus CYVCV to citrus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang et al (2019) reported that D. citri can be an effective vector for virus CYVCV to citrus. It is also one of the most important citrus pests in the Mediterranean region (Bellows & Meisenbacher, 2007;Martin et al, 2000;Boulahia-Kheder, 2021) including Algeria (Boukhalfa & Bonafonte, 1979).…”
Section: Introductionmentioning
confidence: 99%